Analysis of various optimizers on deep convolutional neural network model in the application of hyperspectral remote sensing image classification - Bera, Somenath; Shrivastava, Vimal K. (International journal of remote sensing, 2020)
Hyperspectral image (HSI) classification is a most challenging task in hyperspectral remote sensing field due to unique characteristics of HSI data. It consists of huge number of bands with strong correlations in the spectral and spatial domains. Moreover, limited training samples make it more challenging. To address such problems, we have presented here a spatial feature extraction technique using deep convolutional neural network (CNN) for HSI classification. As optimizer plays an important role in learning process of deep CNN model, we have presented the effect of seven different optimizers on our deep CNN model in the application of HSI classification. The seven different optimizers used in this study are SGD, Adagrad, Adadelta, RMSprop, Adam, AdaMax, and Nadam. Extensive experimental results on four hyperspectral remote sensing data sets have been presented which demonstrate the superiority of the presented deep CNN model with Adam optimizer for HSI classification.